1998
DOI: 10.1006/viro.1998.9368
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of the Membrane-Spanning Domain of the Human Immunodeficiency Virus Type 1 Vpu Protein

Abstract: The human immunodeficiency virus type 1 (HIV-1) vpu gene product is a class I integral membrane phosphoprotein that is capable of oligomerization. Two distinct biological activities have been attributed to Vpu: induction of CD4 degradation in the endoplasmic reticulum and enhancement of viral particle release from the plasma membrane of infected cells. These two biological activities were shown to involve two separable structural domains: the N-terminal transmembrane (TM) domain and the C-terminal cytoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 37 publications
7
87
0
Order By: Relevance
“…Vpu W22* and VPU I17R impair CD4 and tetherin downregulation. Vpu's transmembrane domain is critical for antagonism of CD4 and tetherin (30,(49)(50)(51)(52). To assess whether SM111-selected mutations in Vpu altered Vpu's ability to modulate these cellular proteins, we transfected an immortalized CD4 ϩ T cell line (CEM) with dual expression plasmids encoding GFP and either wild-type or mutant Vpu sequences and then measured endogenous CD4 and tetherin cell surface expression 24 h later using flow cytometry (Fig.…”
Section: Sm111mentioning
confidence: 99%
“…Vpu W22* and VPU I17R impair CD4 and tetherin downregulation. Vpu's transmembrane domain is critical for antagonism of CD4 and tetherin (30,(49)(50)(51)(52). To assess whether SM111-selected mutations in Vpu altered Vpu's ability to modulate these cellular proteins, we transfected an immortalized CD4 ϩ T cell line (CEM) with dual expression plasmids encoding GFP and either wild-type or mutant Vpu sequences and then measured endogenous CD4 and tetherin cell surface expression 24 h later using flow cytometry (Fig.…”
Section: Sm111mentioning
confidence: 99%
“…Vpu is an 81-residue oligomeric integral membrane protein with an N-terminal 24-residue hydrophobic membrane-spanning domain and a C-terminal cytoplasmic tail (59,61). Amino acids important for receptor binding and degradation have been mapped to the C-terminal region of Vpu and to putative α-helices in the cytoplasmic tail of CD4 (62). Coimmunoprecipitation experiments have shown that Vpu associates with wild-type CD4 or with recombinant proteins containing the CD4 cytoplasmic tail, but it is not yet known if the interaction is direct or indirect (63).…”
Section: Vpumentioning
confidence: 99%
“…This might promote translation of viral versus cellular mRNAs, because translation of mRNAs from many cytolytic animal viruses, including reoviruses, is fairly resistant to high sodium concentrations, whereas high sodium concentrations are inhibitory for the translation of most cellular mRNAs (52)(53)(54)(55)(56)(57). On the other hand, progressive membrane damage is thought to promote cell lysis and virus release, facilitating virus spreading to surrounding cells (9,36). Curiously, our results and those of Duncan et al (26) demonstrate that membrane permeabilization and syncytia formation are not essential steps in the avian reovirus replication cycle, because their inhibition by brefeldin A was not accompanied by a significant reduction in either viral protein synthesis or infectious progeny virus production.…”
Section: Membrane Permeabilization By Avian Reovirus Requires Viral Pmentioning
confidence: 99%